2019
DOI: 10.1016/j.agee.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and vegetation structure of three differently managed temperate grasslands

Abstract: An improved regional assessment of the productivity of grasslands depends on comprehensive knowledge of the interactions between climatic drivers, vegetation properties and human activity. Managed grasslands in Europe display highly dynamic responses, which contribute to the challenge in making representative model simulations. considered individually, the relationship between GEP and above-ground biomass, leaf area and vegetation height appeared to follow unified patterns for all sites. In addition, our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…This upper limit intentionally exceeds the actual management practices and allows us to analyze what can happen if fertilization loads are increased. We computed the corresponding single application amount of manure based on C : N ratio of manure equal to 8.9, which is reported for the sites of DE-Fen, DE-RbW, and DE-Gwg (Fu et al, 2017) and is also similar to values suggested in literature (Sommerfeldt et al, 1988;Nyamangara et al, 1999) or slightly lower (Zhu, 2007;Kumar et al, 2010). The input of P and K is assumed to be proportional to the N input based on assigned N : P and N : K values, guaranteeing non P-or K-limited conditions to the system.…”
Section: Numerical Fertilization Experiments and Climate Change Scenariomentioning
confidence: 54%
See 2 more Smart Citations
“…This upper limit intentionally exceeds the actual management practices and allows us to analyze what can happen if fertilization loads are increased. We computed the corresponding single application amount of manure based on C : N ratio of manure equal to 8.9, which is reported for the sites of DE-Fen, DE-RbW, and DE-Gwg (Fu et al, 2017) and is also similar to values suggested in literature (Sommerfeldt et al, 1988;Nyamangara et al, 1999) or slightly lower (Zhu, 2007;Kumar et al, 2010). The input of P and K is assumed to be proportional to the N input based on assigned N : P and N : K values, guaranteeing non P-or K-limited conditions to the system.…”
Section: Numerical Fertilization Experiments and Climate Change Scenariomentioning
confidence: 54%
“…3 ) concentrations in the water leached at the bottom of the lysimeter. The ScaleX campaign of 2015 (Wolf et al, 2017;Zeeman et al, 2019) provided additional data concerning harvested biomass and its carbon and N content.…”
Section: Study Sites and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-layer snow module is mainly developed based on the Community Land Model (CLM; Oleson et al, 2010) and SNTHERM (Jordan, 1991), while the model is unique in including the gravitational and capillary liquid water flows in the unsaturated snow layer based on van Genuchten's concept of water flow in the unsaturated zone (see Hirashima et al, 2010). In the soil module, freeze-thaw processes in soil based on the freezing-point depression equation (Zhang et al, 2007) are considered in heat conduction and liquid water flow equations.…”
Section: Solvegmentioning
confidence: 99%
“…The model is applied to two sites of managed grassland named the Graswang ( Bavarian Alpine Foreland, which is an area in the south of Germany and north of the Alps (Mauder et al, 2013;Zeeman et al, 2017;Zeeman et al, 2019). The grasses are harvested several times during the growing season defined as the period from April to October.…”
Section: Study Sites and Observational Datamentioning
confidence: 99%